2023
DOI: 10.1002/etc.5596
|View full text |Cite
|
Sign up to set email alerts
|

An Amphibian Metamorphosis Assay Dietary Restriction Study: Lessons for Data Interpretation

Abstract: The amphibian metamorphosis assay (AMA) is a key in vivo endocrine screen to investigate chemicals with potential thyroid activity. The test guidelines and associated guidance consider that treatment‐related effects on thyroid gland histomorphology automatically result in the assay being considered positive for thyroid activity, independent of the direction of change or conflicting results in the other biological endpoints. An AMA study was conducted with five different feeding rations equivalent to 50%, 30%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…The influence of diet type, dietary regime, and dietary quality on standardized developmental toxicity studies using amphibians, such as the AMA and LAGDA, was evaluated recently by Fort et al (2022) and Marini et al (2023). Fort et al (2022) (Leloup & Buscagalia, 1977;Shi, 2000), which is generally consistent with the findings of the present study.…”
Section: Histopathologysupporting
confidence: 89%
See 3 more Smart Citations
“…The influence of diet type, dietary regime, and dietary quality on standardized developmental toxicity studies using amphibians, such as the AMA and LAGDA, was evaluated recently by Fort et al (2022) and Marini et al (2023). Fort et al (2022) (Leloup & Buscagalia, 1977;Shi, 2000), which is generally consistent with the findings of the present study.…”
Section: Histopathologysupporting
confidence: 89%
“…The influence of diet type, dietary regime, and dietary quality on standardized developmental toxicity studies using amphibians, such as the AMA and LAGDA, was evaluated recently by Fort et al (2022) and Marini et al (2023). Fort et al (2022) found developmental delay, as determined by a decreasing trend in stage distribution or median developmental stage at the conclusion of exposure in an AMA study in which larvae were fed ground, liquified frog brittle (FB) (Nasco, Fort Atkinson, WI, USA) regardless of additional iodide supplementation (0.06–0.6 μg/l I − ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations